BAP1 loss is associated with DNA methylomic repatterning in highly aggressive Class 2 uveal melanomas - Field, Matthew G. (Clin Cancer Res, 2019)
PURPOSE: The strong association between BAP1 mutations and metastasizing Class 2 uveal melanoma (UM) suggests that epigenetic alterations may play a significant role in tumor progression. Thus, we characterized the impact of BAP1 loss on the DNA methylome in UM. EXPERIMENTAL DESIGN: Global DNA methylation was analyzed in 47 Class 1 and 45 Class 2 primary UMs and in UM cells engineered to inducibly deplete BAP1. RNA-Seq was analyzed in 80 UM samples and engineered UM cells. RESULTS: Hypermethylation on chromosome 3 correlated with downregulated gene expression at several loci, including 3p21 where BAP1 is located. Gene set analysis of hypermethylated and downregulated genes identified axon guidance and melanogenesis as deregulated pathways, with several of these genes located on chromosome 3. A novel hypermethylated site within the BAP1 locus was found in all Class 2 tumors, suggesting that BAP1 itself is epigenetically regulated. Highly differentially methylated probes were orthogonally validated using bisulfite sequencing, and they successfully distinguished Class 1 and Class 2 tumors in 100% of cases. In functional validation experiments, BAP1 knockdown in UM cells induced methylomic repatterning similar to UM tumors, enriched for genes involved in axon guidance, melanogenesis, and development. CONCLUSIONS: This study, coupled with previous work, suggests that the initial event in the divergence of Class 2 UM from Class 1 UM is loss of one copy of chromosome 3, followed by mutation of BAP1 on the remaining copy of chromosome 3, leading to the methylomic repatterning profile characteristic of Class 2 UMs. TRANSLATIONAL RELEVANCE: We provide evidence that bi-allelic loss of BAP1 leads to extensive methylomic repatterning that results in the highly aggressive Class 2 phenotype, thereby providing a more complete picture of UM genomic evolution and potentially explaining the loss of melanocytic differentiation and gain of neural crest-like migratory behavior in Class 2 UM. Highly differentially methylated sites were identified that could form the basis for liquid biopsy biomarkers. These findings suggest a potential role for DNA methylation modulators in the treatment of UM.